Efektivitas Metode Tarjim terhadap Hafalan Qur’an Santri - Hafizah Hafizah; Laili Ramadhani; Yendri Junaidi (STIKes Ibnu Sina Ajibarang, 2025)
The problem that the researcher encountered was that the process of memorizing students still used their own methods, such as memorizing by repeating the verses to be memorized. This results in students memorizing the Qur’an but not knowing what they are memorizing, then many things happen to forget and exchange almost the same words, often missing a few words or letters in a verse, it is difficult to distinguish verses that are almost the same reading and the memorized memorization does not last long. Therefore, the researcher applies the tarjim method to overcome these problems. The tarjim method is a method of memorizing the Qur'an by emphasizing the use of translation and translation of words so as to help students quickly memorize, understand the verses that are memorized, reduce missing words and letters in the memorized verses, reduce the confusion of words or verses that are almost the same and make memorization last a long time. The purpose of this study is to determine the effectiveness of the tarjim method on the memorization of the Qur'an of MTsS DMP Diniyyah Puteri Padang Panjang students. This type of research is an experimental research with a Posttest Only Control Design, samples are selected using the Purposive Sampling technique. This study uses two sample classes, namely the control class and the experimental class. This research was carried out in the even semester of the 2023/2024 academic year, namely halaqoh class A as an experimental class and halaqoh B as a control class. To take data from the sample, a final test in the form of an oral test is used. The implementation of the tarjim method for the memorization of the Qur'an by MTsS DMP Diniyyah Puteri Padang Panjang students has gone very well. This is evident from the results of the learning implementation supervision instrument whose value is 85.68. The students' memorization results also increased after applying the tarjim method, this is evident from the average of the experimental class of 83.61. And from the results of the hypothesis test, the result of t calculation was 6,310 > t table, which is 1,692, so it can be concluded that h1 is accepted. This means that the implementation of the Tarjim method is effective in the memorization of the Qur'an of MTsS DMP Diniyyah Puteri Padang Panjang students